NEUROSCIENCE & KEPEMIMPINAN: PEMANFAATAN ILMU OTAK DALAM PENGAMBILAN KEPUTUSAN KEPEMIMPINAN - Moh. Hafis Xafier; Farrah Noor Aminah Ilfah; Imroatul Mardiyah; Moh. Isa Anshori (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
In the last decade, neuroscience has emerged as an innovative approach in understanding leadership dynamics, particularly in the decision-making process. While conventional leadership theory focuses on psychological and behavioral aspects, this research explores how neurological mechanisms influence leadership effectiveness. The main objective of this study is to analyze the role of brain science in optimizing leaders' decision-making processes in various organizational contexts. The method used is Systematic Literature Review (SLR), which involves the identification, selection, and critical analysis of relevant scientific literature. The results show that the integration of neuroscience in leadership provides deep insights into emotion regulation, attention, and decision-making under stress. The findings also reveal implementation challenges, including sample limitations, technology access, and organizational cultural differences. The implications of this research are important for both academics and practitioners, emphasizing the need for a multidisciplinary approach and the application of more affordable technologies. This research not only offers a rich conceptual framework but also provides recommendations for future research in overcoming limitations and expanding the applications of neuroscience in leadership.